The history of cardiac xenotransplantation: early attempts, major advances, and current progress - Nicholas R. Hess; David J. Kaczorowski; David J. Kaczorowski (Frontiers in Transplantation, 2023)
In light of ongoing shortage of donor organs for transplantation, alternative sources for donor organ sources have been examined to address this supply-demand mismatch. Of these, xenotransplantation, or the transplantation of organs across species, has been considered, with early applications dating back to the 1600s. The purpose of this review is to summarize the early experiences of xenotransplantation, with special focus on heart xenotransplantation. It aims to highlight the important ethical concerns of animal-to-human heart xenotransplantation, identify the key immunological barriers to successful long-term xenograft survival, as well as summarize the progress made in terms of development of pharmacological and genetic engineering strategies to address these barriers. Lastly, we discuss more recent attempts of porcine-to-human heart xenotransplantation, as well as provide some commentary on the current concerns and possible applications for future clinical heart xenotransplantation.